Proceedings of a Pacific Regional Workshop on Assimilative Capacity of the Oceans for Man's Wastes, April 26-30, 1982, Taipei, Republic of China. - Su, Jong-Ching.; Hung, Tsu-Chang. (Taipei, Republic of China Tah-Jinn Printing Co., Ltd., 1982)
Cover title: Assimilative capacity of the oceans for man's wastes.
Keywords: Waste disposal in the ocean